2017
DOI: 10.3390/rs9040388
|View full text |Cite
|
Sign up to set email alerts
|

A Glacier Surge of Bivachny Glacier, Pamir Mountains, Observed by a Time Series of High-Resolution Digital Elevation Models and Glacier Velocities

Abstract: Surge-type glaciers are characterised by relatively short phases of enhanced ice transport and mass redistribution after a comparatively long quiescent phase when the glacier is virtually inactive. This unstable behaviour makes it difficult to assess the influence of climate change on those glaciers. We describe the evolution of the most recent surge of Bivachny Glacier in the Pamir Mountains, Tajikistan between 2011 and 2015 with respect to changes in its topography and dynamics. For the relevant time span, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…The pattern of glacier speed has also evolved (Figures 2a-2d, S3, and Movie S1). In 2016/2017, the maximum speed appears at the boundary of reservoir/receiving zone near the ELA, which is typical for a glacier surge (Fu et al, 2019;Nuth et al, 2019;Wendt et al, 2017). However, during the 2018 speedup event the maximum speed is observed near the terminus.…”
Section: Glacier Velocity and Its Correlation With Temperaturementioning
confidence: 97%
“…The pattern of glacier speed has also evolved (Figures 2a-2d, S3, and Movie S1). In 2016/2017, the maximum speed appears at the boundary of reservoir/receiving zone near the ELA, which is typical for a glacier surge (Fu et al, 2019;Nuth et al, 2019;Wendt et al, 2017). However, during the 2018 speedup event the maximum speed is observed near the terminus.…”
Section: Glacier Velocity and Its Correlation With Temperaturementioning
confidence: 97%
“…Despite significant recent progress through remote-sensing/field measurements (Immerzeel et al 2014) and model studies of the complex coupled system of debris, ice cliffs, and ponds (Miles et al 2016;Buri et al 2016; Banerjee 2017), significant challenges still remain in understanding these glaciers: we cannot yet predict the long-term changes in the debris cover area or thickness, or the effect of such changes on the future of glaciers and their meltwater production at the scale of the whole Himalaya. Frequent surges and contrasting length changes are not only common in the Karakoram but also in central and northeast Pamir (Dolgoushin and Osipova 1975;Kotlyakov et al 2008;Osipova and Khromova 2010;Holzer et al 2016;Wendt et al 2017), and a recent surge was also reported in eastern Pamir (Shangguan et al 2016). In contrast to the Karakoram, however, existing studies on glacier area and length changes suggest a continuous area loss in northeastern and central Pamir.…”
Section: Mass Changesmentioning
confidence: 99%
“…In the western Pamir, glacier volume evolution seems to be more negative, but is for the first decade of the 2000s still relatively modest (Brun et al, 2017); moreover, satellite images of the past two decades reveal that many glaciers in this region have surged (e.g. Wendt et al, 2017). However, many of the non-surge-type glaciers in the Pamir have been continuously retreating and losing area 1810 N. Mölg et al: Inventory of glaciers and debris cover for Karakoram and Pamir (Holzer et al, 2016;Khromova et al, 2006;Shangguan et al, 2006).…”
Section: Glacier Changesmentioning
confidence: 99%
“…In contrast to this definition, the surging Bivachny glacier tongue was separated from Fedchenko glacier in the confluence region although one can argue that Bivachny is a connected feeder (see Fig. 6 in Wendt et al, 2017). A size filter of 0.02 km 2 was applied to remove small seasonal snowfields and remaining noise.…”
Section: Glacier Definition and Separation Using Drainage Dividesmentioning
confidence: 99%